2018
DOI: 10.1155/2018/8490242
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Grade of Liver Steatosis Is Independently Associated with the Risk of Metabolic Syndrome

Abstract: The aim of the study was to explore (a) prevalence and grade of nonalcoholic fatty liver (NAFL) among outpatients referred for abdominal ultrasound (US) examination and (b) relationship between the presence and severity of liver steatosis and metabolic syndrome (MS). This was a retrospective analysis of patients without history of liver disease examined by abdominal US in the University hospital setting. US was used to detect and semiquantitatively grade (0-3) liver steatosis. Data on patients' age, gender, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…The present study revealed that in advanced liver fibrosis (≥F3) diagnosed by real time elastrography, Fib-4 index and NAFLD fibrosis score, there was a good relation between ultrasound grading of fatty liver and advanced fibrosis. This finding agrees with Mustapic 2018 and his colleagues who concluded that increase the grade of fatty liver by ultrasound associated with increase the degree of liver fibrosis [19]. FIB-4 INDEX and NAFLD-FIBROSIS SCORE are two time-honored non-invasive methods for estimating and monitoring of significant liver fibrosis in patients with NAFLD [10].…”
Section: Discussionsupporting
confidence: 88%
“…The present study revealed that in advanced liver fibrosis (≥F3) diagnosed by real time elastrography, Fib-4 index and NAFLD fibrosis score, there was a good relation between ultrasound grading of fatty liver and advanced fibrosis. This finding agrees with Mustapic 2018 and his colleagues who concluded that increase the grade of fatty liver by ultrasound associated with increase the degree of liver fibrosis [19]. FIB-4 INDEX and NAFLD-FIBROSIS SCORE are two time-honored non-invasive methods for estimating and monitoring of significant liver fibrosis in patients with NAFLD [10].…”
Section: Discussionsupporting
confidence: 88%
“…Third, the ultrasonographic grade of hepatic steatosis was not considered in the present study. Mustapic et al reported that patients with higher ultrasonographic grade of hepatic steatosis significantly more frequently had metabolic syndrome, while the grade of hepatic steatosis did not correlate with the presence of hepatic fibrosis 37 . However, there have been no reports on the clinical importance of the reduction in the number of ultrasonographic findings of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, since NAFLD is closely related to insulin resistance, MetS, and its individual components (T2DM dyslipidaemia, obesity, and arterial hypertension), all NAFLD patients should be evaluated for these conditions by performing simple anthropometric measurements and simple laboratory tests [8,66]. In addition, it has become clear that NAFLD is not only a "liver disease" but also a risk factor for many other extrahepatic diseases, including cardiovascular diseases (CVD), chronic kidney disease (CKD), T2DM, and colorectal cancer [7].…”
Section: What To Search For In a Patient Diagnosed With Nafld?mentioning
confidence: 99%